High dielectric permittivity and low loss tangent of polystyrene incorporated with hydrophobic core–shell copper nanowires. Issue 48 (28th May 2015) - He, Linxiang; Tjong, Sie Chin
<x xml:space="preserve">Abstract</x> Core–shell copper nanowires for improving the dielectric performance of polystyrene.